The Influence of Social Media on People's Political Behavior - Alvinto, Bintang; Irawati; Rusta, Andri; Fajri, Mhd (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Mass communication through social media can be used as a link between political communicators and the public. As a political communication channel, social media can influence and determine political behavior because social media can influence public opinion. Good control of public opinion plays a role in winning the battle for societal influence. For political forces participating in parliamentary elections (such as presidential elections, regional head elections and members of parliament), it is important to use social media effectively to convey political messages. Through social media, the public absorbs the content of political messages more quickly and easily, because every public has access to information without barriers and geographical boundaries. Social media is also a very effective means of communication, especially when conveying information and receiving public feedback. Public feedback can bring closer relations between the political media and the public. In addition, the use of social media is increasingly popular and growing among people today, reaching even remote rural areas. With good information packaging, the public can easily understand the political messages conveyed by the political media. By conveying political messages that are appropriate and carried out effectively, in the end it can arouse public sympathy so that they accept the intentions desired by political communicators.